Artificial Phototropic Systems for Enhanced Light Harvesting Based on a Liquid Crystal Elastomer. (4th May 2021) - Yan, Yichen; Zhao, Yusen; Alsaid, Yousif; Yao, Bowen; Zhang, Yucheng; Wu, Shuwang; He, Ximin
Abstract : Oblique‐incidence‐induced energy‐density loss (OEL) is a universal problem which affects nearly all processes involving electromagnetic waves, especially sunlight harvesting. Technologies (solar concentrating plants, large scale systems, etc.) are developed to address this issue, albeit with limitations such as complex design, large size, and high cost. Inspired by nature, artificial phototropism is developed to accurately follow the light direction without complex motors system and electronical control. However, the existing systems are limited by small tracking operation windows, low robustness, or the requirement of high‐power input. Herein, a system is reported that is versatile, low cost, mechanically strong, and can achieve large‐angle reorientation driven by unconcentrated sunlight. This system is demonstrated to be able to recover the OEL for photovoltaics as well as solar vapor generation (SVG) processes. Compared with the nonphototropic system, it can achieve 447% output in lab and 155% in real‐life applications. The principle behind our artificial phototropic system is universal and can be extended to many optical applications, especially sunlight harvesting. Abstract : A versatile, low‐cost, mechanically strong, unconcentrated sunlight‐driven artificial phototropic system is reported. Benefited from double‐leg and bimorph design, it can bear load and achieve large reorientation angle simultaneously. This system is demonstrated to be able to recover the oblique‐incidence‐induced energy‐density loss for photovoltaics and solar vapor generation processes.